ANALYSIS OF CONSUMER PREFERENCE FOR MEAT AND FISH CONSUMPTION IN KADUNA METROPOLIS, KADUNA STATE, NIGERIA - Balogun, O. S.; Akinyemi, M.; Adeosun, S. L. (FUDMA Journal of Sciences, 2023)
The study examined the consumption pattern of meat and fish in Kaduna State, Nigeria. Cross sectional data was used for the study. Multi-stage sampling procedure was used to select 416 respondents with the aid of structured and pre-tested questionnaire. Descriptive statistics and regression analysis were used to analyze the data. The age distribution of the sampled consumers indicated that 66.1% were male between the ages of 31-45 years, with 67.6% of them married and 62.11% having tertiary education. 55% of the respondents had household sizes that ranges between 1 and 5 members Also, 41.42% of the sampled household had their primary occupation as civil servants, and 40.20% preferred beef to other animal protein source. While About 32% gave taste as a major factor influencing their choice. Ordinary least square analysis shows the R2 value to be 89.21%. This implies that about 89% of variables included in the model were responsible for determining variability of animal protein in the study area. Also, the study established that age, marital status, educational level, availability of substitute, and expenditure on food items are factors influencing the consumption of animal protein in the study area. The study concluded that meat was the most preferred animal protein in the study area. It is therefore recommended that education of the consumer should be channeled through a mass and printed media. Public enlightenment on dietary issues must be embarked on by the government. Mass campaign on importance of protein consumption should be embarked on by relevant stakeholders.